Randomised aspirin assignment and risk of adult-onset asthma in the Women's Health Study. Issue 6 (13th March 2008) - Kurth, T; Barr, R G; Gaziano, J M; Buring, J E
Abstract : Background: Randomised data in men show a small but significant reduction in the risk of adult-onset asthma among those given aspirin. The results from an observational study in women suggest that frequent use of aspirin decreases the risk of adult-onset asthma, but randomised data in women are lacking. A study was undertaken to test the effect of 100 mg aspirin or placebo on alternate days on the risk of adult-onset asthma in the Women's Health Study. Methods: A randomised, double-blind, placebo-controlled clinical trial of aspirin and vitamin E was performed in apparently healthy women with no indication or contraindication to aspirin therapy and no history of asthma at study entry. Female health professionals self-reported an asthma diagnosis on yearly questionnaires. Results: Among 37 270 women with no reported history of asthma prior to randomisation and during 10 years of follow-up, there were 872 new cases diagnosed with asthma in the aspirin group and 963 in the placebo group (hazard ratio 0.90; 95% CI 0.82 to 0.99; p = 0.027). This apparent 10% lower relative risk of incident adult-onset asthma among those assigned to aspirin was significantly modified by body mass index, with no effect in women with a body mass index of ⩾30 kg/m2 . The effect of aspirin on adult-onset asthma was not significantly modified by age, smoking status, exercise levels, postmenopausal hormone use or randomised vitamin E assignment. Conclusions: In this large randomised clinical trial of apparently healthy adult women, administration of 100 mg aspirin on alternate days reduced the relative risk of a newly reported diagnosis of asthma. Trial registration number: NCT00000479